The Effect of Managerial Short-Termism on Cost Stickiness of Firms Listed on Tehran Stock Exchange - Zohreh Hajiha; Kaveh Ghaderi; Salah E Din Ghaderi (Journal of Asset Management and Financing, 2019)
Objective: Cost and expense stickiness is an important issue in accounting and economics research, and the literature has shown that cost stickiness cannot be separated from managers’ motivations. This study examines the relationship between managerial short-termism and Cost Stickiness. Method: To measure managerial short-termism were used three criteria discretionary accruals and the actual items (through manipulation of sales and a reduction in discretionary spending) and also other control variables affecting cost stickiness such as the number of the staff, the amount of assets, and sales decline continuous, natural logarithm 1 in addition to the yield of initial annual share, free cash flow, constant payment to managers. Sampling population of the present study includes 95 accepted companies at Tehran stock exchange and manufacturing parts in the time period of 2005-2014. Results: Based on the findings the effects of earnings management based on actual items through reduction in discretionary spending on cost Stickiness is confirmed and can say managerial short-termism has a negative and meaningful relationship with cost stickiness.